Pemikiran Filsuf Muslim di Wilayah Barat - Zaprulkhan, Zaprulkan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
Abstract Islamic philosophy is one part of the tradition of Islamic thought that has developed, both in the East and the West of Islam. In the western part of Islam, Islamic philosophy developed rapidly in the region of Cordova as our mother Andalusia, Spain. It was in the Western region of Islam that a number of well-known philosophers emerged, such as Ibn Bajjah, Ibn Thufail, and Ibn Rusyd. These three great philosophers are very eloquent in developing various philosophical discourses with their unique characteristics which differ from one another. This article tries to explore the philosophical thinking of the three philosophers, and at the end of the discussion is given a critical note on all three of their thoughts. Abstrak Filsafat Islam adalah salah satu bagian dari tradisi pemikiran Islam yang telah berkembang, baik di Timur maupun di Barat Islam. Di bagian barat Islam, filsafat Islam berkembang pesat di wilayah Cordova sebagai ibu kotaAndalusia, Spanyol. Di wilayah barat Islam inilah sejumlah filsuf terkenal muncul, seperti Ibn Bajjah, Ibn Thufail, dan Ibn Rusyd. Ketiga filsuf besar ini sangat fasih dalam mengembangkan berbagai wacana filosofis dengan karakteristik unik mereka yang berbeda satu sama lain. Artikel ini mencoba mengeksplorasi pemikiran filosofis dari tiga filsuf, dan pada akhir diskusi diberikan catatan kritis pada ketiga pemikiran mereka.